2020
DOI: 10.1152/jn.00617.2019
|View full text |Cite
|
Sign up to set email alerts
|

The “embreathment” illusion highlights the role of breathing in corporeal awareness

Abstract: Recent theories posit that physiological signals contribute to corporeal awareness, the basic feeling that one has a body (body ownership) that acts according to one’s will (body agency) and occupies a specific position (body location). Combining physiological recordings with immersive virtual reality, we found that an ecological mapping of real respiratory patterns onto a virtual body illusorily changes corporeal awareness. This new way of inducing a respiratory bodily illusion, called “embreathment,” reveale… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
69
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
2

Relationship

4
6

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 42 publications
6
69
1
Order By: Relevance
“…In all conditions, participants were first given the opportunity to embody the rubber hand by performing tapping movements with their index finger while observing the rubber hand tap synchronously. This procedure generates a sensation of ownership of the rubber hand because the visual appearance of the moving hand conforms to proprioceptive changes due to the participants' finger movements (supported by an anatomically plausible orientation of the rubber hand; e.g., Fusco et al, 2020;Monti et al, 2020;Tieri et al, 2015a;Tieri et al, 2015b). Afterwards, we applied one of three manipulations.…”
Section: Introductionmentioning
confidence: 99%
“…In all conditions, participants were first given the opportunity to embody the rubber hand by performing tapping movements with their index finger while observing the rubber hand tap synchronously. This procedure generates a sensation of ownership of the rubber hand because the visual appearance of the moving hand conforms to proprioceptive changes due to the participants' finger movements (supported by an anatomically plausible orientation of the rubber hand; e.g., Fusco et al, 2020;Monti et al, 2020;Tieri et al, 2015a;Tieri et al, 2015b). Afterwards, we applied one of three manipulations.…”
Section: Introductionmentioning
confidence: 99%
“…Immersive virtual reality (IVR) has proven to be an invaluable tool for exploiting full-body illusion paradigms, wherein a person's real body is replaced with a virtual one and an illusory feeling of BO over the virtual body (VB) is created (the body swap illusion; 7,8). Studies indicate that mere observation of a VB from a first-person perspective (1PP; i.e., aligned with and spatially matching one's own real body) is sufficient to induce illusory BO (9)(10)(11)(12). Recent IVR studies have shown that illusory BO can affect people's perceptions and behavior as well as their implicit attitudes, depending on conspicuous features of the VB (13) such as ethnicity (14), age (15), size (15,16), and sex (9,17).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, such enhanced role of visual information from the virtual scene can provide ample opportunities for experimental manipulations of body ownership by maintaining the visuo-proprioceptive information constant. For example, it allows creating a mismatch between the movements performed by the virtual and the real body, which the participant remains unaware of 32,33 .…”
mentioning
confidence: 99%